Pembelajaran Fikih Berbasis Teknologi Informasi dan Komunikasi - Solikhin, Solikhin; Winarti , Ika (ILJ: Islamic Learning Journal, 2025)
The development of information and communication technology (ICT) has brought significant changes in the world of education, including in learning fiqh subjects in Islamic educational institutions. This research aims to find out how the implementation of ICT-based fiqh learning in MA Al Urwatul Wutsqo Jombang, as well as to identify the supporting and inhibiting factors. The research method used is qualitative with a case study approach. Data collection techniques were conducted through observation interviews and documentation. The results showed that fiqh learning at MA Al Urwatul Wutsqo has integrated various ICT media, such as PowerPoint, learning videos, interactive quiz applications (Quizizz, Kahoot), and the Google Classroom platform. This approach has been proven to increase learning interest, student engagement, and understanding of fiqh material, especially on the practical aspects of worship. Teachers play an active role in designing interactive and contextual learning by utilising available technology. Supporting factors for the success of ICT-based learning include the availability of supporting facilities in the madrasah, support from the principal, teacher training, and students' enthusiasm for digital media. Meanwhile, inhibiting factors include limited equipment and students' uneven ability to use technology.